On the metal cooperativity in a dinuclear copper-guanidine complex for aliphatic C−H bond cleavage by dioxygen - Schön, Florian; Greb, Lutz; Leingang, Simone; Kaifer, Elisabeth; Himmel, Hans-Jörg (Chemistry - a European journal, 2019)
Selective oxidation reactions of organic compounds with dioxygen using molecular copper complexes are of relevance to synthetic chemistry as well as enzymatic reactivity. In the enzyme peptidylglycine α-hydroxylating monooxygenase (PHM), the hydroxylating activity towards aliphatic substrates arises from the cooperative effect between two copper atoms, but the detailed mechanism has yet to be fully clarified. Herein, we report on a model complex showing hydroxylation of an aliphatic ligand initiated by dioxygen. According to DFT calculations, the proton-coupled electron-transfer (PCET) process leading to ligand hydroxylation in this complex benefits from cooperative effects between the two copper atoms. While one copper atom is responsible for dioxygen binding and activation, the other stabilizes the product of intramolecular PCET by copper-ligand charge transfer. The results of this work might pave the way for the directed utilization of cooperative effects in oxidation reactions.